EMPOWERING STUDENTS’ WRITING ABILITY THROUGH ANIMATION MOVIES: A CLASSROOM STUDY AT SMK NEGERI 1 BAUBAU: - - La Mido, La Mido; Irjanti Herman, Ary (English Education Journal, 2025)
This research explored the use of Animation Movies as a medium to enhance the narrative writing skills of eleventh-grade students in the Accountancy Department at SMK Negeri 1 Baubau. The main aim of this experimental study was to determine whether Animation Movies have a significant impact on improving students’ narrative writing abilities.The study employed a pre-test–post-test control group design. The population consisted of all eleventh-grade Accountancy Department students. A total of 50 students were selected as the sample using cluster random sampling. One group of twenty-five students received instruction through Animation Movies, while the remaining twenty-five students were taught using conventional methods. A writing test served as the instrument for data collection.The results indicated that Animation Movies had a significant positive effect on students’ narrative writing performance. At the 0.05 significance level and with 38 degrees of freedom, the t-count of 1.863 exceeded the t-table value of 1.684. Based on this finding, the researcher concluded that teaching narrative writing through Animation Movies was more effective than using traditional teaching techniques for students at SMK Negeri 1 Baubau.